Penn world table 7.0: are the data flawed? (2012)
Penn World Table (PWT) 7.0 is the newest PWT data set, based in part on benchmarked prices collected in 2005. In theory the data in PWT 7.0 should be more accurate than the data in PWT 6.3 since 1996 and similar in earlier years. I show that PWT 7.0 GDP/capita and price data for 1970 to 1996 deviate substantially from prior PWT data that are benchmarked to prices across countries for those years. I conclude that overall the PWT 7.0 data are much less accurate than the data in PWT 6.2 and 6.3.